Defining Electronic Health Record Standards for Child Health: A State-of-the-Art Review - Shafi, Obeid; Liu, Daniel; Thompson, Cori; Margo, Todd; Bennett, Timothy; Suresh, Srinivasan; Yu, Feliciano (Applied Clinical Informatics, 2024)
Background Improving child health using health information technology (IT) requires a unique set of functionalities that are built into the electronic health record (EHR) and are used to support patient care. In this article, we review and discuss the milestones preceding the development of a new child health EHR standard and describe the salient features of this contemporary standard.Methods and Results The Health Level Seven Pediatric Care Health IT Functional Profile (HL7 PCHIT FP) is an informative standard that encompasses the EHR functions required to care for patients less than 21 years of age in any clinical setting, developed to address the pediatric-specific functionality gaps in the EHR. It includes criteria that support communication between providers and all caregivers, inclusion of pediatric-specific vital signs and diagnosis, support for transition to adult care, and support for reporting and documentation of child abuse or neglect including communication with involved authorities. EHR functionalities for documentation and reporting of newborn screening tests with follow-up for abnormal results and functionality for children with special health care needs with support for identifying patients who may benefit from care coordination are also incorporated, in addition to school-based linkages enabling communication between the health care system and their school environment.Conclusion The HL7 PCHIT FP is envisioned to be another vital step towards improving pediatric health by enhancing EHRs to address the unique health IT needs of children and their health providers. While the HL7 PCHIT FP is the most recently published standard on pediatric EHR systems, standards development is an iterative process, and recommendations for continuous refinement and additional functionalities for the next standards release are encouraged.
Keywords: electronic health record; health level seven; child health; policy